Impact of Androgen Deprivation Therapy on Cardiovascular Outcomes in Prostate Cancer - Laurence Klotz; Stephen Van Komen; Sanja Dragnic; William B. White (Société Internationale d’Urologie Journal)
PurposeSubstantial evidence indicates that men with prostate cancer are at an increased risk for cardiovascular disease, and medical and surgical androgen deprivation therapy is associated with further increased cardiovascular risk. There are conflicting reports of differences in cardiovascular safety between gonadotropin-releasing hormone (GnRH) agonists and antagonists. The purpose of this narrative review is to compare data on the cardiovascular risks and safety outcomes associated with different hormonal treatment options in prostate cancer patients and to provide guidance on how to manage the increased risk associated with the condition.MethodsA PubMed search was conducted for papers published in the last 15 years using the following MeSH terms: “prostate neoplasms,” “gonadotropin-releasing hormone,” “androgen agonist,” “androgen antagonists,” “cardiovascular disease,” “epidemiology.”ResultsEvidence regarding the risk of cardiovascular events during treatment with GnRH agonists and antagonists is conflicting. Some retrospective studies have shown that agonists are associated with a greater risk of cardiovascular disease and cardiovascular mortality and morbidity, and a similar risk with agonists and combined androgen blockade. Some studies have reported that antagonists are associated with a decreased risk of cardiovascular mortality and morbidity compared with agonists. With respect to coronary heart disease, ischemic heart disease, myocardial infarction, stroke, or sudden cardiac death, current evidence has failed to demonstrate a significant difference between antagonists and agonists. Cardiovascular risks in patients should be mitigated by regular monitoring of blood pressure, blood glucose, and lipids, as well as counseling patients to abstain from alcohol and improve their diet and exercise. Statins, metformin, and aspirin should also be considered.